GLOBAL PERSPECTIVES ON BUDGETARY SLACK: A COMPREHENSIVE BIBLIOMETRIC ANALYSIS FOR EMERGING RESEARCH TRENDS - Agustina, Rachma; Falikhatun, Falikhatun (Akurasi : Jurnal Studi Akuntansi dan Keuangan, 2025)
This study aims to evaluate the global research development on budgetary slack, including its historical evolution, current state, and future direction. Using bibliometric analysis through the PRISMA Protocol and VOS Viewer, this research analyzes 53 Scopus-indexed articles from 2014 to 2024 out of 170 identified studies. The findings indicate a dominance of quantitative methods (43 articles), with the United Kingdom and the United States having the highest number of publications. The main topics frequently studied include budget participation, honesty, experimentation, trust, and information asymmetry. Author collaboration analysis reveals weak research networks, highlighting opportunities to strengthen interconnections. This study provides insights for regulators and organizations to improve budgeting policies and transparency. Future research should explore governance mechanisms, behavioral factors, technological innovations, industry-specific differences, and ethical aspects of budgetary slack.